D2 Cerebrospinal fluid biomarkers in huntington's disease. (13th September 2016) - Niemelä, Valter; Blennow, Kaj; Landtblom, Anne-Marie; Sundblom, Jimmy
Abstract : Background: Neurofilament light chain (NFL) is an important protein in the cytoskeleton, and it is generally accepted as a marker of permanent neuronal damage. The NFL level in CSF has gained clinical use as a prognostic marker in neurological diseases like Amyotrophic Lateral Sclerosis, Multiple Sclerosis and Alzheimer's disease. It has also been suggested to be a marker of disease stage in Huntington's disease (HD) in two previous studies, with a linear association to levels of mutant Huntingtin. Aim: To validate the proposed role of NFL as a reliable clinical biomarker for disease stage in HD. Methods: CSF samples from manifest HD-patients (n = 12) and premanifest HD-gene expansion carriers (n = 11) were obtained by lumbar puncture. The subjects were assessed with UHDRS total motor score, the cognitive-s test battery, Functional Assessment and Total Functional Capacity to characterise disease stage. NFL was quantified by ELISA (ng/ml). Control samples obtained in identical fashion (n = 5) were analysed to assess sample quality. A validated standard reference range for NFL measured in CSF is available. Results: Pending. NFL values will be available in July 2016 in time to be presented at the EHDN Plenary Meeting in The Hague. Conclusion: This is a cross sectional study to evaluate CSF biomarkers. Longitudinal sampling is needed to further establish their roll and usefulness. NFL is not a disease-specific biomarker, but is clinically available in many hospital labs, unlike for instance mtHTT assays.